Quantitatively Predicting Bacterial Adhesion Using Surface Free Energy Determined with a Spectrophotometric Method - Zhang, Xinru (Environ Sci Technol, 2015)
Bacterial adhesion onto solid surfaces is of importance in a wide spectrum of problems, including environmental microbiology, biomedical research, and various industrial applications. Despite many research efforts, present thermodynamic models that rely on the evaluation of the adhesion energy are often elusive in predicting the bacterial adhesion behavior. Here, we developed a new spectrophotometric method to determine the surface free energy (SFE) of bacterial cells. The adhesion behaviors of five bacterial species, Pseudomonas putida KT2440, Salmonella Typhimurium ATCC 14028, Staphylococcus epidermidis ATCC 12228, Enterococcus faecalis ATCC 29212, and Escherichia coli DH5α, onto two model substratum surfaces, i.e., clean glass and silanized glass surfaces, were studied. We found that bacterial adhesion was unambiguously mediated by the SFE difference between the bacterial cells and the solid substratum. The lower the SFE difference, the higher degree of bacterial adhesion. We therefore propose the use of the SFE difference as an accurate and simple thermodynamic measure for quantitatively predicting bacterial adhesion. The methodological advance and thermodynamic simplification in the paper have implications in controlling bacterial adhesion and biofilm formation on solid surfaces.